Phosphorescent material and preparation method thereof
The polymer nanoparticles with the polyamine are prepared by reacting alkane polycarboxylic acid with the polyamine through high-temperature calcination, which solves the problems of high toxicity and high cost in traditional phosphorescent materials, and realizes efficient and stable preparation of phosphorescent materials, which is suitable for a variety of high-tech fields.
Patent Information
- Application Number
- CN202311315539.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional phosphorescent materials have disadvantages such as high toxicity, high cost, complex preparation, and easy to be quenched by ambient oxygen, and are difficult to meet the application needs of modern high-tech fields.
By mixing alkane polycarboxylic acid with polyamine and reacting by high-temperature calcination, polyamide or polyimide product with low molecular weight is generated, and impurities are removed by reverse dispersion-reprecipitation method to prepare polymer nanoparticles with self-assembly phosphorescence enhancement characteristics.
It realizes efficient preparation of phosphorescent materials, has better stability and extended phosphorescence emission time, and is suitable for biomedical, optoelectronic devices, anti-counterfeiting and information encryption systems and other fields.
Smart Images

Figure CN119799319A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a phosphorescent material and a preparation method thereof, and belongs to the field of energy nanomaterials. Background Art
[0002] Traditional phosphorescent materials usually include organometallic composites and pure organic compounds, which generally have disadvantages such as high toxicity, high cost, complex preparation, and easy quenching by oxygen in the environment. Polymer nanoparticles with phosphorescent effect have attracted extensive attention due to their extremely long phosphorescent emission lifetime, large Stokes shift, high environmental sensitivity, and minimal interference from short-lived autofluorescence and scattered light. At present, they have shown broad application prospects in advanced fields such as anti-counterfeiting, information encryption, sensing and catalysis.
[0003] Self-assembly refers to the spontaneous formation of structures with unique characteristics through the interaction of intermolecular forces, so that individual molecules form directional and orderly structures. The orderly connection of primitives through non-covalent bonds forms assemblies with specific structures or functions, which has shown great application potential in biology, chemistry, physics, medicine and other fields. Summary of the invention
[0004] In one aspect of the present application, a phosphorescent material is provided, namely, a polymer nanoparticle with self-assembled phosphorescence enhancement properties, wherein the phosphorescent material is a polymer nanoparticle;
[0005] The polymer is a polyamide compound;
[0006] The molecular weight of the polymer is 1000-12000 Da.
[0007] Optionally, the molecular weight of the polymer is independently selected from any value among 1000Da, 2000Da, 3000Da, 4000Da, 5000Da, 6000Da, 7000Da, 7500Da, 8000Da, 9000Da, 10000Da, 11000Da, 12000Da or a range between any two of the above.
[0008] Optionally, the size of the polymer nanoparticles is 2 to 5 nm.
[0009] Optionally, the size of the polymer nanoparticles is independently selected from any value of 2 nm, 2.5 nm, 2.6 nm, 2.8 nm, 3 nm, 3.1 nm, 3.4 nm, 4 nm, or a range between any two of the above values.
[0010] Optionally, the phosphorescent material has a phosphorescent luminescence time of 0.01 to 10 s.
[0011] Optionally, the phosphorescent emission time of the phosphorescent material is independently selected from any value among 0.01s, 2s, 4s, 6s, 7s, 8s, 9s, 10s or a range between any two of the above values.
[0012] Optionally, the polymer is selected from at least one of polyethyl succinic acid diamide, polyethyl glutaric acid diamide, polyethyl tetrafluorosuccinic acid diamide, polyethyl oxalic acid diamide, polyethyl malonic acid diamide, and polyethyl adipate diamide.
[0013] Another aspect of the present application provides a method for preparing the above-mentioned phosphorescent material, wherein an alkane polycarboxylic acid and a polyamine compound are ground and mixed, and reacted by a high-temperature calcination method under an inert gas purge condition, and a polyamide or polyimide product with a low molecular weight is generated by controlling the reaction temperature, reaction time and precursor. After the reaction is completed, the unreacted precursor or impurities in the product are removed by a reverse dispersion-reprecipitation method to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties.
[0014] The preparation method comprises:
[0015] The phosphorescent material is obtained by grinding and calcining a mixture containing alkane polycarboxylic acid and polyamine.
[0016] Optionally, the alkane polycarboxylic acid is selected from at least one of glutaric acid, succinic acid, tetrafluorosuccinic acid, oxalic acid, malonic acid and adipic acid.
[0017] Optionally, the polyamine is ethylenediamine.
[0018] Optionally, the molar ratio of the alkane polycarboxylic acid to the polyamine is 1:1-5.
[0019] Optionally, the molar ratio of the alkane polycarboxylic acid to the polyamine is independently selected from any value of 1:1, 1:1.2, 1:1.5, 1:2, 1:3, 1:4, 1:5 or a range between any two of the above values.
[0020] Optionally, the calcination temperature is 100 to 230°C;
[0021] The calcination time is 2 to 6 hours.
[0022] Optionally, the calcination temperature is independently selected from any value of 100°C, 150°C, 180°C, 200°C, 230°C or a range between any two of the above values.
[0023] Optionally, the calcination time is independently selected from any value among 2h, 4h, 6h or a range between any two of the above.
[0024] Optionally, the calcination is performed under an atmosphere of nitrogen and / or air.
[0025] Optionally, the preparation method further comprises:
[0026] After calcination, the obtained product is dispersed in a solvent, filtered and dried to obtain the phosphorescent material.
[0027] Optionally, the solvent is selected from a combination of dimethyl sulfoxide-water, dimethyl sulfoxide-ethanol, methanol-acetonitrile, chloroform-toluene, and acetone-n-hexane.
[0028] Optionally, the drying temperature is 40 to 70° C., and the drying time is 5 to 10 hours.
[0029] Optionally, the drying temperature is independently selected from any value of 40°C, 45°C, 50°C, 60°C, 70°C or a range between any two of the above values.
[0030] Optionally, the drying time is independently selected from any value among 5h, 6h, 8h, 10h or a range between any two of the above.
[0031] As a specific implementation, the method for preparing the phosphorescent material comprises the following steps:
[0032] (1) Alkane polycarboxylic acid and polyamino compound are ground and mixed, and reacted by high temperature calcination under the condition of inert gas purge.
[0033] (2) By controlling the precursors, reaction temperature, reaction time, etc., a polyamide or polyimide product with a low molecular weight is generated.
[0034] (3) After the reaction is completed, the unreacted precursor or impurities in the product are removed by a dispersion-reprecipitation method, and the polymer nanoparticles with self-assembled phosphorescence enhancement properties are obtained after filtering and drying.
[0035] Wherein, the solvent described in step (3) comprises: one of the combination of dimethyl sulfoxide-water, dimethyl sulfoxide-ethanol, methanol-acetonitrile, chloroform-toluene, and acetone-n-hexane;
[0036] In the present application, the yield of the phosphorescent material, ie, polymer nanoparticles with self-assembled phosphorescence enhancement properties, is 70-95%.
[0037] The present application utilizes polymer nanoparticles with self-assembled phosphorescence-enhancing properties to achieve controllable preparation, have better stability, and effectively extend the phosphorescence emission time. Therefore, polymer nanoparticles with self-assembled phosphorescence-enhancing properties have great application prospects in many high-tech fields such as biomedicine, optoelectronic devices, anti-counterfeiting and information encryption systems.
[0038] The beneficial effects of this application include:
[0039] (1) The high-temperature calcination method using inert gas purge can inhibit the side reactions induced by water or other low molecular weight intermediates produced during the polycondensation process, greatly reducing the by-products in the final product;
[0040] (2) The dispersion-precipitation method can greatly reduce the difficulty of the preparation process and effectively improve the yield of the product;
[0041] (3) The prepared product can produce phosphorescence;
[0042] (4) The phosphorescence intensity and particle size of the prepared product can be controlled by the concentration in the dispersed system;
[0043] (5) The phosphorescence behavior of the product can be controlled by adjusting the reaction time;
[0044] (6) This method has the characteristics of simple synthesis, high product yield, few product impurities, and enhanced product self-assembly phosphorescence. It has great application prospects in the fields of anti-counterfeiting, information encryption, sensing, bioimaging, light-emitting diodes, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the fluorescence emission spectrum of the polymer nanoparticles with self-assembled phosphorescence enhancement properties in Example 1 of the present application.
[0046] Figure 2 This is the fluorescence excitation spectrum of the polymer nanoparticles with self-assembled phosphorescence enhancement properties in Example 1 of the present application.
[0047] Figure 3 This is the ultraviolet absorption spectrum of the self-assembled polymer nanoparticles with enhanced phosphorescence properties in Example 1 of the present application.
[0048] Figure 4 This is the XRD spectrum of the polymer nanoparticles with self-assembled phosphorescence enhancement properties in Example 1 of the present application.
[0049] Figure 5 This is the infrared spectrum of the self-assembled polymer nanoparticles with enhanced phosphorescence properties in Example 1 of the present application. DETAILED DESCRIPTION
[0050] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0051] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0052] In the embodiments of the present application, the fluorescence spectrum testing instrument is a fluorescence spectrophotometer, and the testing conditions are a voltage of 400 V and a slit of 5 nm;
[0053] The instrument used for the UV absorption spectrum test is a UV spectrophotometer, and the test conditions are a test range of 200-700nm;
[0054] The instrument used for the XRD spectrum test is an X-ray diffractometer, and the test conditions are a scanning angle of 20-90°.
[0055] The infrared spectrum test was performed using an infrared spectrometer with a scanning range of 500-4000cm -1 .
[0056] Example 1
[0057] At room temperature, 1.0 mol of glutaric acid and 1.0 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 minutes, and then slowly heated to 200°C, reacted for 2 hours, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 5.0 mL of dimethyl sulfoxide, and then 50.0 mL of water was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 6 hours to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethylglutaric acid diamide, the molecular weight of the polymer was 7000 Da, the size of the polymer nanoparticles was 2.5 nm, the phosphorescence emission time was 0.01 to 7 s, and the solid powder yield was 82%.
[0058] Figure 1 The fluorescence emission spectrum of the polymer nanoparticles with self-assembled phosphorescence enhancement properties prepared for this example is as follows: Figure 1 It can be seen that the optimal emission wavelength is 440nm.
[0059] Figure 2 The fluorescence excitation spectrum of the polymer nanoparticles with self-assembled phosphorescence enhancement characteristics prepared in this embodiment is as follows: Figure 2 It can be seen that the optimal excitation wavelength is 375 nm.
[0060] Figure 3 The ultraviolet absorption spectrum of the self-assembled polymer nanoparticles with enhanced phosphorescence prepared in this example is as follows: Figure 3 It can be seen that there is a strong absorption peak around 260nm.
[0061] Figure 4 The XRD spectrum of the self-assembled polymer nanoparticles with enhanced phosphorescence prepared in this example is as follows: Figure 4 It can be seen that absorption peaks appear around 20° and 35°.
[0062] Figure 5The infrared spectrum of the self-assembled polymer nanoparticles with enhanced phosphorescence prepared in this example is as follows: Figure 5 It can be seen that the polymer nanoparticles have abundant functional groups such as C=O and OH.
[0063] Example 2
[0064] At room temperature, 1.0 mol of succinic acid and 1.2 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 minutes, and then slowly heated to 180°C. After reacting for 4 hours, the mixture was cooled to room temperature and the product was ground into powder. The solid powder was dispersed in 5.0 mL of dimethyl sulfoxide, and then 50.0 mL of ethanol was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 8 hours to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethylsuccinic acid diamide, the molecular weight of the polymer was 8000 Da, the size of the polymer nanoparticles was 2.8 nm, the phosphorescence emission time was 0.01 to 7 s, and the solid powder yield was 83%.
[0065] Example 3
[0066] At room temperature, 1.0 mol of tetrafluorosuccinic acid and 1.5 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace. Nitrogen was introduced for 15 minutes, and then slowly heated to 200°C. After reacting for 6 hours, the mixture was cooled to room temperature and the product was ground into powder. The solid powder was dispersed in 5.0 mL of methanol, and then 50.0 mL of acetonitrile was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 8 hours to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethyltetrafluorosuccinic acid diamide, the molecular weight of the polymer was 6000 Da, the size of the polymer nanoparticles was 3.1 nm, the phosphorescence emission time was 0.01 to 7 s, and the solid powder yield was 79%.
[0067] Example 4
[0068] At room temperature, 1.0 mol of oxalic acid and 1.0 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 min, and then slowly heated to 180°C, reacted for 2 h, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 3.0 mL of chloroform, and then 30.0 mL of toluene was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 10 h to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was poly(ethylene oxalic acid diamide), the molecular weight of the polymer was 7000 Da, the size of the polymer nanoparticles was 3.4 nm, the phosphorescence emission time was 0.01 to 9 s, and the solid powder yield was 85%.
[0069] Example 5
[0070] At room temperature, 1.0 mol of malonic acid and 1.2 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace. Nitrogen was introduced for 15 min, then slowly heated to 180°C, reacted for 4 h, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 3.0 mL of acetone, and then 30.0 mL of n-hexane was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 8 h to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethylmalonic acid diamide, the molecular weight of the polymer was 8000 Da, the size of the polymer nanoparticles was 2.8 nm, the phosphorescence time was 0.01 to 9 s, and the solid powder yield was 83%.
[0071] Example 6
[0072] At room temperature, 1.0 mol of adipic acid and 1.2 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 minutes, and then slowly heated to 200°C, reacted for 6 hours, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 5.0 mL of dimethyl sulfoxide, and then 50.0 mL of water was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 6 hours to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethyl adipamide, the molecular weight of the polymer was 5000 Da, the size of the polymer nanoparticles was 2.6 nm, the phosphorescence time was 0.01 to 8 s, and the solid powder yield was 78%.
[0073] Example 7
[0074] At room temperature, 1.0 mol of glutaric acid and 1.2 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 min, and then slowly heated to 200°C, reacted for 2 h, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 5.0 mL of dimethyl sulfoxide, and then 50.0 mL of water was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 6 h to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethylglutaric acid diamide, the molecular weight of the polymer was 6000 Da, the size of the polymer nanoparticles was 3.4 nm, the phosphorescence emission time was 0.01 to 7 s, and the solid powder yield was 80%.
[0075] Example 8
[0076] At room temperature, 1.0 mol of glutaric acid and 1.0 mol of ethylenediamine were weighed and uniformly mixed and transferred to a muffle furnace, nitrogen was introduced for 15 minutes, and then slowly heated to 200°C, reacted for 4 hours, and then cooled to room temperature, and the product was ground into powder. The solid powder was dispersed in 5.0 mL of dimethyl sulfoxide, and then 50.0 mL of water was added for precipitation. The obtained precipitate was filtered and vacuum dried at 60°C for 6 hours to obtain polymer nanoparticles with self-assembled phosphorescence enhancement properties. The polymer was polyethylglutaric acid diamide, the molecular weight of the polymer was 7500 Da, the size of the polymer nanoparticles was 2.8 nm, the phosphorescence emission time was 0.01 to 7 s, and the solid powder yield was 85%.
[0077] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A phosphorescent material, characterized in that: The phosphorescent material is polymer nanoparticles; The polymer is a polyamide compound; The molecular weight of the polymer is 1000-12000 Da.
2. The phosphorescent material according to claim 1, characterized in that The size of the polymer nanoparticles is 2-5 nm.
3. The phosphorescent material according to claim 1, characterized in that: The phosphorescent material has a phosphorescent luminescence time of 0.01 to 10 seconds.
4. The phosphorescent material according to claim 1, characterized in that: The polyamide compound is selected from at least one of polyethyl succinic acid diamide, polyethyl glutaric acid diamide, polyethyl tetrafluorosuccinic acid diamide, polyethyl oxalic acid diamide, polyethyl malonic acid diamide and polyethyl adipate diamide.
5. A method for preparing the phosphorescent material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The phosphorescent material is obtained by grinding and calcining a mixture containing alkane polycarboxylic acid and polyamine.
6. The preparation method according to claim 5, characterized in that: The alkane polycarboxylic acid is at least one selected from glutaric acid, succinic acid, tetrafluorosuccinic acid, oxalic acid, malonic acid, and adipic acid.
7. The preparation method according to claim 5, characterized in that: The polyamine is at least one of ethylenediamine and phenylenediamine.
8. The preparation method according to claim 5, characterized in that: The molar ratio of the alkane polycarboxylic acid to the polyamine is 1:1-5.
9. The preparation method according to claim 5, characterized in that: The calcination temperature is 100-230°C; The calcination time is 2 to 6 hours; The calcination is performed under an atmosphere of nitrogen and / or air.
10. The preparation method according to claim 5, characterized in that: The preparation method further comprises: After calcination, the obtained product is dispersed in a solvent, filtered, and dried to obtain the phosphorescent material; Preferably, the solvent is selected from the group consisting of dimethyl sulfoxide-water, dimethyl sulfoxide-ethanol, methanol-acetonitrile, chloroform-toluene, and acetone-n-hexane; Preferably, the drying temperature is 40-70° C., and the drying time is 5-10 hours.